Mengenal Keindahan Susunan Bahasa Al-Qur’an Melalui Al-Istikhdam dan Al-Istithrad - Imas Marliana; Farhatul Fadhilah; Harun Al-Rasyid (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This study explores the concepts of Al-Istikhdam and Al-Istithrad as part of stylistic devices in the Arabic rhetoric discipline (balaghah). Al-Istikhdam refers to the use of a single word with two different meanings in a specific context, while Al-Istithrad involves the insertion of additional sentences or ideas without deviating from the main discussion. The study aims to identify the application of these two concepts in classical Arabic texts, particularly in literary and rhetorical works. The method employed is textual analysis of primary sources such as the Qur'an, hadith, and classical poetry. The findings reveal that Al-Istikhdam is used to enrich meanings and refine stylistic expression, whereas Al-Istithrad functions to provide additional explanations that strengthen the main argument without disrupting narrative flow. This research is expected to offer new insights into the beauty and complexity of the Arabic language and its contribution to the development of balaghah studies.